Ketuhanan Dalam Siwa Siddhanta - Luh Kartika Dewi; Ni Putu Sinta Oktaviani; Putu Eka Arsadi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The journal entitled Deity in Siwa Siddhanta was chosen based on the author's idea, this journal is organized based on various understandings. This journal focuses on Shiva Siddhanta. Saiva Siddhanta is an understanding which contains the teachings of Lord Siva. In this journal, we review how the history of the development of Shiva Siddhanta from India to Indonesia, what are the sources of Shiva Siddhanta's teachings and how the application of Shiva Siddhanta in Bali. The author takes this title so that those who read this journal can understand the essence of the Divinity journal in Shiva Siddhanta. Hinduism in the archipelago or Hinduism in Bali is characterized by the Shiva Siddhanta sect. Although the teachings or sect of Siwa Siddhanta originated from India, in Bali, Siwa Siddhanta has united with the existing culture in the archipelago.